Ryanodine receptor 1 (RYR1) mutations in two patients with tubular aggregate myopathy. (13th June 2022) - Vattemi, Gaetano Nicola Alfio; Rossi, Daniela; Galli, Lucia; Catallo, Maria Rosaria; Pancheri, Elia; Marchetto, Giulia; Cisterna, Barbara; Malatesta, Manuela; Pierantozzi, Enrico; Tonin, Paola; Sorrentino, Vincenzo
Abstract: Two likely causative mutations in the RYR1 gene were identified in two patients with myopathy with tubular aggregates, but no evidence of cores or core‐like pathology on muscle biopsy. These patients were clinically evaluated and underwent routine laboratory investigations, electrophysiologic tests, muscle biopsy and muscle magnetic resonance imaging (MRI). They reported stiffness of the muscles following sustained activity or cold exposure and had serum creatine kinase elevation. The identified RYR1 mutations (p.Thr2206Met or p.Gly2434Arg, in patient 1 and patient 2, respectively) were previously identified in individuals with malignant hyperthermia susceptibility and are reported as causative according to the European Malignant Hyperthermia Group rules. To our knowledge, these data represent the first identification of causative mutations in the RYR1 gene in patients with tubular aggregate myopathy and extend the spectrum of histological alterations caused by mutation in the RYR1 gene. Abstract : Identification of RYR1 mutations uncovers the fourth gene causative of tubular aggregate myopathy.